Aberrant expression of microRNAs and the miR‐1/MET pathway in canine hepatocellular carcinoma. (3rd January 2018) - Lai, Y.‐C.; Ushio, N.; Rahman, M. M.; Katanoda, Y.; Ogihara, K.; Naya, Y.; Moriyama, A.; Iwanaga, T.; Saitoh, Y.; Sogawa, T.; Sunaga, T.; Momoi, Y.; et al.
Abstract : Canine hepatocellular carcinoma (HCC) is the most common primary hepatic tumour in dogs. MicroRNA (miRNA) dysregulation has been reported in human HCC and shown to have diagnostic and prognostic value; however, there are no data on miRNA expression in canine HCC. The aim of the present study was to investigate differentially expressed miRNAs in canine HCC. Analysis of miRNA expression in canine HCC tissues and cell lines by quantitative reverse transcription PCR showed that miR‐1, miR‐122, let‐7a, and let‐7g were downregulated, whereas miR‐10b and miR‐21 were upregulated in canine HCC. MET is one of the target genes of miR‐1. MET was upregulated in canine HCC at the gene and protein levels, and a significant correlation between the concomitant downregulation of miR‐1 and upregulation of MET was observed. Fast/intermediate‐proliferating canine HCC cell lines had higher MET gene and protein expression levels than the slow‐proliferating cell line. These findings suggest that miRNAs are differentially expressed in canine HCC, and that the miR‐1/MET pathway may be associated with canine HCC cell proliferation.